Electrodeposited folic acid platinum electrode for rapid detection of human hepatocellular carcinoma cells - Dhayal M.; Srivastava S.; Jaiswal J. (My University, 2025)
Folic acid (FA) was successfully adhered onto the surface of platinum through an electrochemical process without hindering its functional capability to bind with human hepatocellular carcinoma (HepG2) cells. The CV response of FA-deposited platinum electrode showed distinct oxidation and reduction peaks, which decreased gradually by varying the concentrations of FA. The electrochemically deposited FA/Pt electrode was used to detect HepG2 cells in the electrolyte, and a linear response in DPV peak current was observed with a sensitivity of ∼ 3 nA/cells mL−1 in the range of 5×103 to 25×103 cells mL−1. © 2023 Wiley-VCH GmbH.